Multiple bile duct anastomoses without stent in living-donor liver transplant. Issue 5 (September 2009) - Haberal, Mehmet; Sevmis, Sinasi; Karakayali, Hamdi; Moray, Gokhan; Torgay, Adnan; Arslan, Gulnaz
Aims: It is unclear whether the presence of multiple bile ducts in the graft increases the risk of biliary complications after living-donor liver transplant. In this study, we present our results to identify risk factors for the development of biliary complications and to determine the effect of multiple bile ducts in the incidence of biliary complications after living-donor liver transplant.Materials & methods: A total of 106 living-donor liver transplants were performed since 2006 and were divided into two groups: those with a single bile duct (n = 70) and those with multiple bile ducts (n = 36). Duct-to-duct biliary anastomosis was used in 79 (75.5%) living-donor liver transplants and a Roux-en-Y-hepaticojejunostomy was used in the remaining 27 (24.5%).Results: The overall biliary complications rate was 12.2% (four leaks, seven stenoses, two leaks plus stenoses). All biliary complications were treated using interventional radiologic techniques. Only hepatic arterial complications were a significant risk factor for the development of biliary complications. During the mean follow-up, 11.1 ±± 4.2 months (range: 1––28 months), 16 recipients died (15%) and the remaining 89 recipients (85%) are alive with normal liver function.Conclusions: We found that only hepatic arterial complications were associated with a higher rate of biliary complications. Although our follow-up period was short, the presence of more than one bile duct in the graft does not appear to increase the risk of biliary complications after living-donor liver transplant.